Individual’s Creativity and Entrepreneurial Intention: A Moderating Role of Family and University - Habib, Nazan; Khoso, Sania Haq; Shujjauddin, Arbab Muhammad (Pakistan Languages and Humanities Review, 2022)
Entrepreneurship is widely recognized for its contributions to economic growth, innovation, and employment. This study explores the relationship between individual creativity and entrepreneurial intention, as well as the impact of family support and university creativity on entrepreneurial aspirations. The findings reveal a positive association between individual creativity and entrepreneurial intention, supporting the notion that higher levels of creativity increase the likelihood of having entrepreneurial aspirations. Similarly, a positive relationship between creativity within the family and entrepreneurial intention was observed. However, no significant relationship between creativity in the university and entrepreneurial intention was found. These results emphasize the importance of individual creativity and a supportive family environment in shaping entrepreneurial aspirations. Further research is needed to explore additional factors that influence entrepreneurial intention and validate these findings.